Chemically defined stem cell microniche engineering by microfluidics compatible with iPSCs' growth in 3D culture. (January 2022) - Liang, Wanjun; Li, Yan; Cuellar-Camacho, Jose Luis; Yu, Leixiao; Zhou, Suqiong; Li, Wenzhong; Haag, Rainer
Abstract: The development of induced pluripotent stem cell (iPSCs) has opened unprecedented opportunities for biomedical applications, but poorly defined animal-derived matrices yield cells with limited therapeutic value. Considerable challenges remain in improving cell-culturing approaches to create the conditions for iPSCs' reliable expansion. Herein we report the development of a chemically defined, artificial three-dimensional (3D) microniche for iPSCs' growth and reliable expansion, constructed with degradable polyethyleneglycol-co-polycaprolactone and RGDfk-functionalized dendritic polyglycerol precursors according to bioorthogonal strain-promoted azide-alkyne cycloaddition by droplet-based microfluidics. This compatible microniche can allow for the robust production of iPSCs that maintain high pluripotency expression and excellent viability without pathogen or immunogen transfer risks. This microniche technology shows great promise in enabling iPSCs to achieve their full therapeutic potential. Graphical abstract: A chemically defined 3D microniche compatible with iPSCs' growth was engineered based on new degradable polyethyleneglycol-co-polycaprolactone and RGDfk-functionalized dendritic polymers. It can support iPSCs' robust proliferation and maintain high pluripotency without risks of pathogen and immunogen transfer. The fabrication process of this engineered microniche is performed under microfluidic conditions with high efficiency and shows great promise for iPSCs' culture on large scale. Image 1